Materials Formed by Combining Inorganic Glasses and Metal-Organic Frameworks - Chester, Ashleigh M.; Castillo-Blas, Celia; Wondraczek, Lothar; Keen, David A.; Bennett, Thomas D. (Chemistry - A European Journal, 2022)
Here, we propose the combination of glassy or crystalline metal-organic frameworks (MOFs) with inorganic glasses to create novel hybrid composites and blends.The motivation behind this new composite approach is to improve the processability issues and mechanical performance of MOFs, whilst maintaining their ubiquitous properties. Herein, the precepts of successful composite formation and pairing of MOF and glass MOFs with inorganic glasses are presented. Focus is also given to the synthetic routes to such materials and the challenges anticipated in both their production and characterisation. Depending on their chemical nature, materials are classified as crystalline MOF-glass composites and blends. Additionally, the potential properties and applications of these two classes of materials are considered, the key aim being the retention of beneficial properties of both components, whilst circumventing their respective drawbacks.
CRIS-Team Scopus Importer:2023-04-20
Keywords: hybrid composite; hybrid glass; metal-organic framework; new materials